2020
DOI: 10.2174/1573403x15666191203110554
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related Effects of Resveratrol in Different Models of Pulmonary Arterial Hypertension: A Systematic Review

Abstract: Background: Pulmonary arterial hypertension (PAH) is a severe and progressive disease of pulmonary arterioles. This pathology is characterized by elevation of the pulmonary vascular resistance and pulmonary arterial pressure, leading to right heart failure and death. Studies have demonstrated that resveratrol possesses a protective effect in the mechanisms related to the genesis of the PAH-induced by different models. Objective: This study aimed to investigate the dose-related effects of resveratrol in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…For example, resveratrol enhances the expression of Nrf2 in myocardium and, thus, alleviates myocardial ischemia-reperfusion injury (Schreiber et al, 2019;Xu et al, 2019). Administration of resveratrol is shown to retard the progression of pulmonary arterial hypertension (Ferreira et al, 2019). Treatment with resveratrol attenuates isoprenaline-related cardiotoxicity in Wistar rats (Sammeturi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, resveratrol enhances the expression of Nrf2 in myocardium and, thus, alleviates myocardial ischemia-reperfusion injury (Schreiber et al, 2019;Xu et al, 2019). Administration of resveratrol is shown to retard the progression of pulmonary arterial hypertension (Ferreira et al, 2019). Treatment with resveratrol attenuates isoprenaline-related cardiotoxicity in Wistar rats (Sammeturi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why a single dose of resveratrol (10 mg/Kg/day) is used in our study is that, to the best of our knowledge, there is no conclusive evidence of what would be the best dose of resveratrol for health benefits; the more recent studies in animal models show that both low (<20 mg/Kg/day) and high (>30 mg/Kg/day) doses of resveratrol have similar effect sizes on clinical outcomes such as ischemia/reperfusion injury ( Xue et al, 2022 ) and pulmonary arterial hypertension ( Ferreira et al, 2020 ). Unfortunately, at the date of writing this study, there is no meta-analytic evidence on the most useful dose for the protection of oxidative stress, so we consider it widely useful to evaluate a single low dose to reduce the confounding factor of dose-dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of polyphenols on hypertension and vascular dysfunction as key components of metabolic syndrome have been widely studied. Bioactives under investigation include hesperidin (Valls et al, 2021), anthocyanins (Igwe et al, 2019), grape seed polyphenols (Schön et al, 2021), or resveratrol (Breuss et al, 2019) (Ferreira et al, 2020), for which global genomic effects have been reported in publications included in our study. Meta-analyses of human intervention studies showed modest effects of various polyphenols or polyphenol-rich foods on blood pressure when compared with antihypertensive drugs (Zhang et al, 2016) (Sahebkar et al, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%